2009
DOI: 10.1387/ijdb.082823kh
|View full text |Cite
|
Sign up to set email alerts
|

The Xenopus Bowline/Ripply family proteins negatively regulate the transcriptional activity of T-box transcription factors

Abstract: Bowline, which is a member of the Xenopus Bowline/Ripply family of proteins, represses the transcription of somitogenesis-related genes before somite segmentation, which makes Bowline indispensable for somitogenesis. Although there are three bowline/Ripply family genes in each vertebrate species, it is not known whether the Bowline/Ripply family proteins share a common role in development. To elucidate their developmental roles, we examined the expression patterns and functions of the Xenopus Bowline/Ripply fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
(60 reference statements)
2
18
0
Order By: Relevance
“…Tbx1 is also expressed in the otic placode, whereas Ripply3 is expressed in the pronephros. Similar results were reported for Tbx1 (Ataliotis et al, 2005;Showell et al, 2006) and for Ripply3 (Hitachi et al, 2009). Quantitative real-time RT-PCR (QPCR) analysis showed that Ripply3 is expressed maternally.…”
Section: Tbx1 and Ripply3/dscr6 Are Expressed In The Ppesupporting
confidence: 79%
See 1 more Smart Citation
“…Tbx1 is also expressed in the otic placode, whereas Ripply3 is expressed in the pronephros. Similar results were reported for Tbx1 (Ataliotis et al, 2005;Showell et al, 2006) and for Ripply3 (Hitachi et al, 2009). Quantitative real-time RT-PCR (QPCR) analysis showed that Ripply3 is expressed maternally.…”
Section: Tbx1 and Ripply3/dscr6 Are Expressed In The Ppesupporting
confidence: 79%
“…Control embryos were injected with 20 ng standard control MO: CCT CTT ACC TCA GTT ACA ATT TAT A (GeneTools). The following plasmids were constructed by PCR amplification of the protein-coding regions of the indicated genes and cloning into the expression vector pCDG1: xRARa2.2 (Sharpe, 1992), xTbx1 (Ataliotis et al, 2005) and xRipply3 (Hitachi et al, 2009). xRipply3 WRPWrAAAA , xRipply3 FPVQrAAAA and Ripply3…”
Section: Microinjectionmentioning
confidence: 99%
“…Through this screening process, several somitogenesis-related genes, such as paraxial protocadherin and mesogenin 1 (msgn1), as well as a novel gene bowline (Kim et al, 2000;Yoon et al, 2000;Kondow et al, 2006), were isolated. Two bowline-related genes, ledgerline and xRipply3, were also isolated from X. laevis (Chan et al, 2006;Hitachi et al, 2008). Counterparts have been identified in the zebrafish and mouse (Ripply1, 2, 3), human (DSCR6), and amphioxus (AmphiSom) (Shibuya et al, 2000;Kawamura et al, 2005;Li et al, 2006;Chan et al, 2007;Morimoto et al, 2007).…”
Section: Identification and Characterization Of Novel Somitogenesis-rmentioning
confidence: 99%
“…To reveal the developmental role of another member of the Ripply family, Ripply3 [also known as Down syndrome critical region 6 (Dscr6)] (Kawamura et al, 2005;Hitachi et al, 2009;Shibuya et al, 2000), we examined its expression and function in the early mouse embryo. On finding that both Ripply3 and Tbx1 are expressed in the pharyngeal endoderm, we examined the role of Ripply3 by generating Ripply3-deficient mice and investigated its relationship with Tbx1.…”
Section: Introductionmentioning
confidence: 99%